2019
DOI: 10.1177/1120672119861623
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravitreal dexamethasone implants in the treatment of diabetic macular edema: Expert recommendations using a Delphi approach

Abstract: Objective: The aim of this study is to develop guidance on the use of intravitreal dexamethasone implants in the treatment of diabetic macular edema. Method: The study was performed using the modified Delphi method to obtain a consensus among a panel of experts on management of patients with diabetic macular edema and use of intravitreal dexamethasone implants in clinical practice. Thirty-seven panel members, experts on retina, from different Spanish centers were invited to participate. Individual and anonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In practice, a physician may switch to intravitreal corticosteroid if DME persists after the anti-VEGF loading phase. 7,8 Early switching in nonresponders could benefit visual outcome. 5,6 Therefore, these patients, together with those who require frequent anti-VEGF injections, were all classified into group 2 in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, a physician may switch to intravitreal corticosteroid if DME persists after the anti-VEGF loading phase. 7,8 Early switching in nonresponders could benefit visual outcome. 5,6 Therefore, these patients, together with those who require frequent anti-VEGF injections, were all classified into group 2 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It could also reduce the treatment burden and improve patient compliance. 7,8 Multimodal images are useful tools for the diagnosis and the monitoring of DME. Fluorescein angiography (FA) has been regarded as the gold standard for evaluating microvascular structural and functional changes in retinal vascular diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spanish MOMENTUM-D study group has concluded that DEX implant is particularly beneficial in the DME treatment in patients with a history of major cardiovascular event, vitrectomized patients, pseudophakic patients, non-compliant patients, patients requiring cataract surgery, and patients with substantial inflammatory component. The consensus paper has also recommended that switching to DEX implant should be considered after three anti-VEGF injections[ 42 ].…”
Section: Expert Recommendations For the Management Of Dme With Dex Implant In Real-life Practicementioning
confidence: 99%
“…The experts' panel agreed that intravitreal dexamethasone implants are useful in the treatment of patients with DME with different profiles. 122 Examples of such patients include pseudophakic, poor adherents, vitrectomized, candidates for cataract surgery, patients with a high inflammatory component, and with a history of cardiovascular events. The use of intravitreal dexamethasone reduces the number of visits and facilitates compliance.…”
Section: Introductionmentioning
confidence: 99%